The Functional Role of Fecal Microbiota Transplantation on Dextran Sulfate Sodium-Induced Colitis in Mice - He, Yan; Li, Xueting; Yu, Hengyuan; Ge, Yixuan; Liu, Yuanli; Qin, Xiaofa; Jiang, Mingshan; Wang, Xiuhong (Frontiers in Cellular and Infection Microbiology, 2019)
Increasingly studies revealed that dysbiosis of gut microbiota plays a pivotal role in the pathogenesis of ulcerative colitis (UC). Fecal microbiota transplantation (FMT) has drawn more and more attention and become an important therapeutic approach. This study aims to examine the facts about the effective components and look into potential mechanisms of FMT. Colitis was induced by 3% (w/v) dextran sulfate sodium (DSS) in drinking water for 7 days. Colitis mice were administered by oral gavage with fecal suspension, fecal supernatant, fecal bacteria, or boiling-killed fecal bacteria from healthy controls and the disease activity index was monitored daily. On the seventh day, mice were euthanized. The length, histological score, parameters related to inflammation, gut barrier functions of the colon, activities of digestive protease and β-glucuronidase in feces were measured. All of the four fecal components showed certain degree of efficacy in DSS-induced colitis, while transplantation of fecal suspension showed the most potent effect as demonstrated by less body weight loss, lower disease activity scores, more expression of tight junction proteins and TRAF6 and IκBα, less expression of TNF-α, IL-1β, IL-10, TLR-4, and MyD88 in gut tissue, as well as restoration of fecal β-glucuronidase and decreases in fecal digestive proteases. These results provide a novel insight into the possible mechanism of FMT and may help to improve and optimize clinical use of FMT.